Å kjøpe for Norge - Langseth, Marius; Similä, Jan Ole (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"How does the public sector manage the vast sums spent annually on goods and services? For individual municipalities, counties, and state agencies it is, in practical terms, about obtaining resources that enable them to deliver the services they are obligated to deliver. For Parliament and the government, it is not just about securing the production of goods and services here and now, but about how we ensure good and consistent standards of welfare in the future as well. In addition, there are high expectations that purchases occur in sustainable, efficient, and intelligent ways and that suppliers are challenged to think creatively - to be innovative. As for buyers, a greater degree of professionalization within public procurement practices is expected. In this anthology we have brought together several authors who are contributing new research focused on how public sector procurements are carried out in Norway. Topics range from questions around outsourcing, how the procurement function is organized, contract administration, purchaser competence, and the use of data analytics. Readers will also find a review of Norwegian research on public procurement published in international journals over the past two decades. "